EFFECTIVENESS OF AN EXERCISE TRAINING PROGRAM ON YOUTH WITH ASPERGER SYNDROME - Borremans, Erwin; Rintala, Pauli; Kielinen, Marko (European Journal of Adapted Physical Activity, 2009)
Although exercise training programs are effective in improving physical fitness and motor competence in typically developing youth, insufficient data of the impact of interventions are available in youth with Asperger syndrome (AS). The purpose of this study was to examine the efficacy of an exercise program as part of an ongoing vocational training program for adolescents with AS on motor competence and physical fitness. Twenty adolescents with AS (mean age = 16.8yrs) were enrolled in this study. A quasi-experimental nonequivalent-control-group design with a follow-up measurement over a period of six months was followed. The intervention group received a 12-week physical exercise program focusing on improving motor competence and physical fitness. The structured activity program was applied 3 days a week for 1 hour. Data collection included pre-, post-, and follow-up evaluations using the Movement Assessment Battery for Children (M-ABC-II) and the EUROFIT physical fitness test together with training diaries and comments from teachers and guardians. Two 2X3 repeated measures ANOVAs indicated improved motor competence and physical fitness that was sustained over time. The exercise training program was successful with adolescents with AS and implementation of similar programs is therefore recommended.
Keywords: Asperger syndrome; exercise; training program; physical activity; motor skills; physical fitness; M-ABC-II; EUROFIT; youth